Factors Related to Nurse Behavior in Medical Waste Management Efforts at the Cilegon City Regional General Hospital in 2022 - Maman Sutisna; Nurce Arifiati (UJoST- Universal Journal of Science and Technology, 2022)
Medical waste management is an action taken on medical waste, which starts from the collection stage to the final processing stage. This study aims to determine the factors related to the behavior of nurses in efforts to manage medical waste in Cilegon City Hospital in 2022. The method used in this study was analytical observational with a cross sectional design. The number of respondents in this study were 63 respondents. The sampling technique used was proportional sampling with univariate and bivariate analysis using the Chi Square test. The results of this study showed that 50.8% of respondents with D3 education, 63.5% had good knowledge, and 50.8% had a positive attitude in medical waste management. The results of the relationship test showed that there was a significant relationship between knowledge and behavior of nurses in medical waste management efforts (Pv = 0.003; OR = 6.026), there was no significant relationship between education and attitudes with nurses' behavior in medical waste management efforts (Pv = 0.689 ; OR=1.397), and (Pv=0.536; OR=1.563). Cilegon City Hospital needs to increase the knowledge of nurses by conducting socialization regarding the sorting and storage of medical waste by the sanitasi.